Johnny Appleseed : a story about John Chapman - Montgomery, Herb.; Henstra, Friso (Minneapolis, MN : Winston Press, 1979)
Briefly relates how Johnny Appleseed spread apple trees and a love of God across the frontier.
Keywords: Appleseed, Johnny, -- 1774-1845 -- Juvenile literature; Appleseed, Johnny, -- 1774-1845.; Apple growers -- United States -- Biography -- Juvenile literature; Frontier and pioneer life -- Middle West -- Juvenile literature; Frontier and pioneer life